THE IMPORTANCE OF PEDAGOGICAL COMMUNICATION IN FOREIGN LANGUAGE LEARNING BY CHILDREN WITH SPECIAL EDUCATIONAL NEEDS - Kekosh, M.L (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The article investigates the role of pedagogical communication in inclusive education. The basic principles of inclusive education are analyzed. The advantages of communicative interaction of teachers, assistants, psychologists, parents and students in an inclusive class are determined. Various methods of communicative interaction between all participants of the educational process are offered. The importance of teaching foreign languages to children with special educational needs to achieve greater social integrity, for personal development, access to information, employment, mobility, social interaction, cultural enrichment, development of intercultural awareness is proved. The process of learning a foreign language as an effective tool for intellectual, personal and professional development of a child with special needs is characterized, which contributes to the successful integration into society. The reasons for obstacles and barriers to learning and full participation of each child in the educational process are given. The peculiarities of teaching foreign languages to children with special educational needs, which ensure successful learning of schoolchildren, are outlined. The main ways to improve the teaching of foreign languages to children with special educational needs are considered: individualization and differentiation of education, adaptation of educational courses, use of information technologies, play activities. The important role of formation of inclusive competence of a foreign language teacher is determined. The positive influence of the friendly atmosphere in the class on the acquisition of a foreign language by pupils with special educational needs is highlighted. The importance of using a multisensory approach in teaching foreign languages in an inclusive class is proved. Recommendations for successful implementation of inclusive education are offered. The main activity of a foreign language teacher in an inclusive class is highlighted: organization of a special communicative educational environment.